Quality of life in Vietnamese young adults: A validation analysis of the World Health Organization’s quality of life (WHOQOL-BREF) instrument - Vu, Linh Gia; Nguyen, Long Hoang; Nguyen, Cuong Tat; Vu, Giang Thu; Latkin, Carl A.; Ho, Roger C. M.; Ho, Cyrus S. H. (Frontiers in Psychiatry, 2022)
Background: The abbreviated version of the World Health Organization’s Quality of Life (WHOQOL-BREF) instrument has been widely used to assess the quality of life (QOL) of different population groups. Aims: This study aimed to examine the validity and reliability of the Vietnamese version of WHOQOL-BREF in evaluating the QOL of Vietnamese young adults. Methods: The WHOQOL-BREF was validated in an online cross-sectional study among 445 young adults from 16-35 years in Vietnam. The exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were performed to examine the factorial structure of the instrument. The reliability and validity of the new factorial model were evaluated. Results: The EFA and CFA suggested the 3-factor model had better fit models than the theoretical 4-factor model. The internal consistency of factor 1 “External life” and factor 2 “Internal life” were excellent (0.931) and good (0.864), respectively, while the internal consistency of factor 3 “Physical and mental health” was nearly acceptable (0.690). Results indicated that the 3-factor model had good convergent and divergent validity as well as moderate discriminant validity. Scores of factors “External life” and “Internal life” had significant predictive effects on general QOL, general health, and overall QOL (p<0.05). Meanwhile, factor 3 “Physical and mental health” could only predict general health and overall QOL (p<0.05). Conclusion: This validation study improves understanding of the characteristics of QOL among young adults in Vietnam. While the theoretical model of WHO can be utilized for global comparisons, a new local model should be considered and cross-culturally adapted to successfully capture the progress of public health interventions for promoting young adults’ quality of life.